The Role of Community College: Navigating the Issues and Interventions of Mabalacat City College Amidst COVID Pandemic - Glen S. Nolasco; John Dave Dicuangco; Michelle Aguilar-Ong; Marilyn S. Arcilla (Advanced Journal of STEM Education, 2024)
The COVID-19 pandemic has generated a myriad of issues in educational systems across the globe. This community-based study aims to navigate the issues encountered by professors of Mabalacat City College during the pandemic and the interventions employed to address these issues. This study used a descriptive survey research design. In this study, a purposive sampling method was employed to obtain 27 professors. Survey questionnaires were distributed using Google Forms to the participants at Mabalacat City College. The data obtained from the participants were subject to the data privacy act. Thematic analysis and descriptive statistics were used to analyze the participants’ data. The results revealed two major themes faced during the pandemic which are “technical problems” and “classroom management”. The study found that the installation of DigiHubs provided opportunities for learners experiencing difficulties during the pandemic. These DigiHubs have various means, such as internet connection, gadgets, modules, and learning spaces, that foster a conducive environment. In addition, workshops/training sessions, seminars, and webinar sessions empowered technophobic professors who adhered to traditional modalities. Hence, these findings underscore the critical role of community colleges in the educational system, particularly during times of crisis.